Diseño de un Sistema de Generación Eléctrica Fotovoltaica para la Comunidad Amaichon en el Corregimiento Mayapo, Municipio de Manaure, Departamento de La Guajira (2023)
This project has as objective; design a photovoltaic electricity generation system for the Amaichon community in the corregimiento of Mayapo, Manaure Municipality. Electricity services are essential for the integral development of a population and its inhabitants. The sun is a source of energy that contributes to science to find sustainable alternatives for vulnerable peoples. The study methodology had a quantitative approach, a design proposal for a photovoltaic power generation system was presented, establishing its cost benefit. The results obtained show that the implementation of this photovoltaic electricity generation system will benefit the 19 inhabitants who live in 4 houses and do not have energy for their home. It is recommended that the Amaichon community continue with the management of the project in the entities of the Colombian government or organizations that can collaborate in its implementation for the benefit of the population. Also, it is recommended to use not only solar energy, but also wind power generation.